Cultural communication through social media and the second or foreign language lerning - Nasrin, Nipa (BRAC University, 2013)
Foreign or second language learning can be enhanced through the interaction with the target language and cultural context. However, it has always been a great difficulty to create the authentic cultural exchange which can give students a chance of experiencing the target language. For culture based language learning, social media can be a great tool. First, direct communication with the target culture and language will keep the students motivated and give them better language skills and critical literacy. This authentic interaction will ultimately increase their reading, writing and sociocultural knowledge. Second, the interrelation between reading, writing, speaking and the need of critical literacy in learning a language can be emphasized through the use of social medias. Finally, different content-based email or internet projects are important but teachers’ role in making those effective is of prime importance. Teachers have to design the courses considering the benefits and the problems of using internet communication, along with the ways to facilitate the cultural/critical literacy through different later activities. In general, the need of cultural communication in language learning and in achieving critical literacy is undeniable.